2017
DOI: 10.3389/fevo.2017.00092
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Distinguish between Plasticity and Non-random Distributions of Behavioral Types Along Urban Gradients in a Wild Passerine Bird

Abstract: The impact of urbanization has been widely studied in the context of species diversity and life history evolution. Behavioral adaptation, by contrast, remains poorly understood because empirical studies rarely investigate the relative importance of two key mechanisms: plastic responses vs. non-random distributions of behavioral types. We propose here an approach that enables the simultaneous estimation of the respective roles of these distinct mechanisms. We investigated why risky behaviors are often associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 50 publications
0
48
0
Order By: Relevance
“…This agrees with numerous studies showing that urban animals take more risk toward humans than non‐urban animals (Samia et al, ). Personality‐dependent habitat choice may be an important driver of this difference, as a recent study on great tits found that the distribution of individuals in an urban–suburban area was explained by their risk‐taking toward humans, but the birds did not flexibly adjust their avoidance behavior to the level of urbanization (Sprau & Dingemanse, ). Nevertheless, we cannot exclude the possibility that habituation or other forms of behavioral plasticity play a major role in the greater risk‐taking responses in urban great tits compared to conspecifics living in forests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This agrees with numerous studies showing that urban animals take more risk toward humans than non‐urban animals (Samia et al, ). Personality‐dependent habitat choice may be an important driver of this difference, as a recent study on great tits found that the distribution of individuals in an urban–suburban area was explained by their risk‐taking toward humans, but the birds did not flexibly adjust their avoidance behavior to the level of urbanization (Sprau & Dingemanse, ). Nevertheless, we cannot exclude the possibility that habituation or other forms of behavioral plasticity play a major role in the greater risk‐taking responses in urban great tits compared to conspecifics living in forests.…”
Section: Discussionmentioning
confidence: 99%
“…This may happen by differential colonization, when cities are colonized by a subset of individuals that have above‐average general risk‐taking (Møller, ), for example, due to differences in pace‐of‐life syndromes (Charmantier, Demeyrier, Lambrechts, Perret, & Grégoire, ; Sol et al, ). Also, local microevolutionary adaptation in cities may lead to intrinsic differences in general risk‐taking between urban and non‐urban populations (Carrete & Tella, ; Holtmann, Santos, Lara, & Nakagawa, ; Sprau & Dingemanse, ). Furthermore, habituation to human disturbance may also be transferred to other type of threats, resulting in reduced general risk‐taking (McCleery, ).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the relationship between urbanization and EPO occurrence might be non-causal. For example, individuals with different behavioral types can differ in their habitat choice (Holtmann et al, 2017;Sprau and Dingemanse, 2017) and the propensity to engage in EPF can vary between females as part of their personality (Forstmeier, 2007;Forstmeier et al, 2014;Wolak et al, 2018). It is thus possible that a tendency for promiscuity is associated with the behavioral traits that facilitate settlement in cities, such as innovative problem solving and exploratory behavior (Bókony et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, whatever the direction of the effects, they are likely to influence aspects of behavior, physiology, and life history of urban-dwellers in their coping response to the urban environment (Tuomainen and Candolin, 2012;Sprau and Dingemanse, 2017). Consequently, stress-responses, i.e., the behavioral and physiological means by which animals cope with environmental stress, play an important role in local adaptation (Badyaev, 2005).…”
Section: Introductionmentioning
confidence: 99%